Separator and manufacturing method thereof
Patent Information
- Application Number
- JP2023203662
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-11
- Filing Date
- 2023-12-01
- Publication Date
- 2025-02-25
AI Technical Summary
【0022】 本発明の利点、特徴及び実現方法は、より理解しやすいように、例示的な実施形態を参照してより詳細に説明する。また、本発明は、異なる形態で実現することも可能である。そのため、本明細書に記載された実施形態に限定されることは理解されるべきではない。逆に、提供される実施形態は、当技術分野に通常の知識を有する者にとって、本発明の範疇をより徹底的かつ完全に伝えるものである。本発明は、添付されている特許出願の範囲にのみ定義されるものである。
Smart Images

Figure 2025026786000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a separator, and more particularly to a method for manufacturing a separator having improved tensile strength and compression resistance. [Background technology]
[0002] Lithium batteries are composed of four main parts: positive electrode material, negative electrode material, separator, and electrolyte. The separator is a thin film with a microporous structure that mainly separates the positive and negative electrodes of the battery to prevent short circuits caused by electrical contact between the electrodes and allows free ions to pass between them. Therefore, the separator has a decisive effect on the discharge rate, energy density, cycle performance, and safety of lithium batteries.
[0003] The separator can be manufactured mainly by two methods: dry stretching and wet stretching. Dry separators are often used in large-sized lithium iron phosphate power lithium batteries due to their high safety and low cost. Wet separators have a thin thickness, high porosity, and uniform pore size, which can provide excellent breathability, while the coating layer of the wet separator must meet the safety requirements of thermal stability and tensile strength.
[0004] As the capacity of batteries increases, it is generally required to make the separator thinner so that ions can shuttle easily. However, the separator itself needs to have a certain mechanical strength during the assembly and charge / discharge cycle of the battery. Therefore, after the separator is thinned, its mechanical strength may decrease, so it is important to increase the mechanical strength of the separator so as to maintain its insulation properties, ion permeability, etc.
[0005] Therefore, to further ensure the safety of the battery, a separator having enhanced mechanical strength is required. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention discloses a separator having improved tensile strength and good compression resistance and a method for manufacturing the same. Meanwhile, the separator according to the present invention has high shrinkage resistance at high temperatures and provides high puncture strength. [Means for solving the problem]
[0007] The separator according to the present invention comprises a reinforced polyolefin porous substrate and an inorganic coating layer. The reinforced polyolefin porous substrate is obtained by subjecting the polyolefin porous substrate to a pre-reinforcing treatment. The inorganic coating layer comprises a plurality of inorganic particles and an adhesive, and is formed on at least one surface of the reinforced polyolefin porous substrate. The pre-reinforcing treatment comprises sequentially applying a 0.1 wt% to 3 wt% titanium alkoxide solution and a 30 wt% to 70 wt% aqueous alcohol solution to the polyolefin porous substrate.
[0008] In the separator of the present invention, the titanium alkoxide used in the titanium alkoxide solution in the pre-strengthening treatment of the reinforced polyolefin porous substrate is methanol titanium, ethanol titanium, titanium isopropanol, titanium (IV) t-butoxide, or a combination thereof, and the solvent of the titanium alkoxide solution is methanol, ethanol, isopropanol, or a combination thereof.
[0009] In the separator according to the present invention, the alcohol aqueous solution in the pre-strengthening treatment of the reinforced polyolefin porous substrate is methanol, ethanol, isopropanol, ethoxyethanol, allyl alcohol, ethylene glycol, or a combination thereof.
[0010] In the separator according to the present invention, the titanium alkoxide solution used in the preliminary reinforcement treatment of the reinforced polyolefin porous substrate further contains 0.5 wt % to 5 wt % of hexamethyldisilazane.
[0011] In the separator according to the present invention, the alcohol aqueous solution used for the preliminary reinforcement treatment of the reinforced polyolefin porous substrate further contains a tackifier, and the amount of the tackifier in the alcohol aqueous solution is 0.01 wt% to 1 wt%.
[0012] In the separator according to the present invention, the tackifier in the alcohol aqueous solution in the preliminary reinforcement treatment of the reinforced polyolefin porous substrate is poly(meth)acrylate, poly-N-vinylacetamide, a crosslinkable (meth)acrylic resin, an acrylonitrile-acrylate copolymer, an acrylonitrile-acrylamide-acrylate copolymer, or a combination thereof.
[0013] In the separator according to the present invention, the inorganic coating layer comprises 1 wt% to 20 wt% of an adhesive and 80 wt% to 99 wt% of a plurality of inorganic particles. In one preferred embodiment of the present invention, the reinforced polyolefin porous substrate may comprise an inorganic coating layer on one or both surfaces. The thickness of the inorganic coating layer is 0.5 μm to 5 μm, preferably 0.5 μm to 3 μm.
[0014] In the separator according to the present invention, the inorganic particles in the inorganic coating layer of the reinforced polyolefin porous substrate are selected from the group consisting of Mg(OH)2, BaSO4, BaTiO3, HfO2, SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al(OH)3, Al2O3, boehmite (AlOOH), SiC, TiO2, and combinations thereof.
[0015] In the separator according to the present invention, the average particle size (D50) of these inorganic particles is 0.1 μm to 2.0 μm.
[0016] In the separator according to the present invention, the adhesive contained in the inorganic coating layer of the reinforced polyolefin porous substrate is ethylene-vinyl acetate copolymer (EVA), poly(meth)acrylate, crosslinkable (meth)acrylic resin, fluorine-based rubber, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinylpyrrolidone (PVP), poly-N-vinylacetamide, polyvinylidene fluoride (PVDF), polyurethane, or a combination thereof.
[0017] In another embodiment of the present invention, a method for producing a separator includes providing a polyolefin porous substrate, and subjecting the polyolefin porous substrate to a pre-strengthening treatment to form a reinforced polyolefin porous substrate, in which a 0.1wt%-3wt% titanium alkoxide solution and a 30wt%-70wt% alcohol aqueous solution are sequentially applied to the polyolefin porous substrate, and an inorganic coating layer comprising a plurality of inorganic particles and an adhesive is applied to at least one surface of the reinforced polyolefin porous substrate.
[0018] In the method for preparing the separator according to the present invention, the phthalein alkoxide used in the titanium alkoxide solution in the pre-strengthening treatment is methanol titanium, ethanol titanium, titanium isopropanol, titanium (IV) t-butoxide or a combination thereof, preferably titanium isopropanol. The solvent of the titanium alkoxide solution is methanol, ethanol, isopropanol or a combination thereof.
[0019] In the method for preparing the separator according to the present invention, the alcoholic solution is methanol, ethanol, isopropanol, ethoxyethanol, allyl alcohol, ethylene glycol, or a combination thereof. In a preferred embodiment of the present invention, the alcoholic solution is methanol, ethanol, isopropanol, or a combination thereof.
[0020] The above invention is intended to provide a simplified summary of the disclosure so that readers have a basic understanding of the disclosure. The summary of the invention in this specification is not a complete summary of the disclosure, and is not intended to indicate important / critical elements of the embodiments of the present invention or to define the scope of the present invention. After referring to the following embodiments, those skilled in the art to which the present invention pertains can easily understand the basic intent of the present invention and the technical means and embodiments adopted by the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] In order to make the disclosure of the present invention more detailed and complete, the following describes the embodiments and specific examples of the present invention. However, this is not the only way to implement or operate the specific embodiments of the present invention. The embodiments disclosed below may be combined with each other or substituted when beneficial. In addition, one embodiment may be added to another embodiment. No further description or explanation is necessary.
[0022] The advantages, features and implementation methods of the present invention will be described in more detail with reference to exemplary embodiments for easier understanding. Also, the present invention can be implemented in different forms. Therefore, it should not be understood that the present invention is limited to the embodiments described herein. On the contrary, the embodiments provided will convey the scope of the present invention more thoroughly and completely to those skilled in the art. The present invention is defined only by the scope of the attached patent application.
[0023] Unless otherwise defined, all terms (including technical and scientific terms) and proper nouns used in the following text have substantially the same meaning as commonly understood by those skilled in the art to which the present invention belongs. For example, terms defined by commonly used dictionaries should be understood to have a meaning consistent with the content of the relevant art. Unless explicitly defined in the following text, they should not be understood in an overly idealized or overly formal sense.
[0024] In the present specification, "(meth)acrylate" refers to methacrylate and acrylate.
[0025] The present invention aims to disclose a separator having improved tensile strength and compression resistance and a method for manufacturing the same. The separator according to the present invention can enhance the tensile strength and compression resistance of the separator without increasing the total thickness of the separator. Meanwhile, the separator according to the present invention has high temperature shrinkage resistance and provides high puncture strength.
[0026] The separator according to the present invention includes a reinforced polyolefin porous substrate and an inorganic coating layer. The reinforced polyolefin porous substrate is obtained by subjecting the polyolefin porous substrate to a preliminary reinforcement treatment. The inorganic coating layer includes a plurality of inorganic particles and an adhesive, and is formed on at least one surface of the reinforced polyolefin porous substrate. In the preliminary reinforcement treatment, a 0.1 wt% to 3 wt% titanium alkoxide solution and a 30 wt% to 70 wt% alcohol aqueous solution are applied to the polyolefin porous substrate in this order.
[0027] In the separator according to the present invention, the reinforced polyolefin porous substrate is formed by forming a titanium oxide and / or titanium hydroxide thin film on the surface and the wall of the porous structure of the polyolefin porous substrate through a preliminary reinforcement treatment, thereby strengthening the structure of the polyolefin porous substrate and avoiding a large difference in material modulus or mechanical strength between the organic polyolefin porous substrate and the inorganic coating layer. As a result, the separator formed after the subsequent application of the inorganic coating layer has an advantageous effect of having reinforced tensile strength and good overall compression resistance.
[0028] The polyolefin porous substrate used in the separator according to the present invention may be, for example, but is not limited to, a single-layer polyethylene or a single-layer polypropylene. In one embodiment of the present invention, the thickness of the polyolefin porous substrate is about 5 micrometers (μm) to 30 μm, preferably 7 μm to 25 μm, and the porosity may be about 30% to 60%.
[0029] In one preferred embodiment of the separator according to the present invention, the preliminary strengthening treatment includes treating the polyolefin porous substrate with a 0.2 wt % to 2.5 wt % titanium alkoxide solution and a 40 wt % to 60 wt % aqueous alcohol solution.
[0030] In one preferred embodiment of the separator according to the present invention, this preliminary strengthening treatment can be repeated as necessary. That is, the polyolefin porous substrate is treated with a titanium alkoxide solution and an aqueous alcohol solution in sequence one or more times. When the strengthening treatment with a titanium alkoxide solution and an aqueous alcohol solution is repeated, the concentrations of the titanium alkoxide solution and the aqueous alcohol solution may be the same or different, as long as they are within the above concentration range disclosed in the present invention.
[0031] In the separator according to the present invention, the titanium alkoxide solution used in the preliminary strengthening process further contains 0.5wt%-5wt% hexamethyldisilazane. The titanium alkoxide solution is stabilized so that the titanium alkoxide does not precipitate early when reacting with the alcohol aqueous solution, but enters the pores of the polyolefin porous substrate and reacts with the alcohol aqueous solution on the porous structure wall to form a composite thin film of titanium oxide and / or titanium hydroxide and hexamethyldisilazane. The amount of hexamethyldisilazane used in the titanium alkoxide solution is preferably 0.5wt%-3wt%, particularly 0.5wt%-2wt%.
[0032] In one preferred embodiment of the separator according to the present invention, the alcoholic aqueous solution used for the preliminary strengthening treatment further contains a tackifier. This strengthens the adhesion between the titanium oxide and / or titanium hydroxide formed by the reaction of the titanium alkoxide with the alcoholic aqueous solution and the surface of the polyolefin porous substrate and the inner wall of the porous structure. Suitable tackifiers include, but are not limited to, poly(meth)acrylate resins, crosslinkable (meth)acrylic resins, poly N-vinylacetamide, acrylonitrile-acrylate copolymers, acrylonitrile-acrylamide-acrylate copolymers, or combinations thereof. In one preferred embodiment of the present invention, one or more tackifiers can be used in the alcoholic aqueous solution.
[0033] In the separator according to the present invention, the amount of the tackifier used in the alcoholic aqueous solution is 0.01 wt % to 1 wt %, preferably 0.05 wt % to 0.5 wt %.
[0034] In the separator according to the present invention, the tackifier suitable for the alcohol aqueous solution may be a commercially available product. For example, BM-950B manufactured by Zeon Corporation, PNVA GE191 series (e.g., GE191-103, GE191-104, GE191-107, or GE191-108) manufactured by Showa Denko K.K., "Soteras" manufactured by Ashland Corporation, USA, TM Examples include the "CCS-V Binder" manufactured by Zhuhai Chenyu New Material Technology Co., Ltd. of China, and the "CYJ-01" manufactured by Zhuhai Chenyu New Material Technology Co., Ltd. of China.
[0035] The alcohol aqueous solution used in the pre-strengthening treatment of the separator according to the present invention may further contain additives such as a flame retardant, an antioxidant, a surface modifier, or an antistatic agent.
[0036] In the preliminary strengthening treatment of the separator according to the present invention, the titanium alkoxide solution and the alcohol aqueous solution can be applied by dip coating or spray coating.
[0037] In the separator according to the present invention, the reinforced polyolefin porous substrate can have an inorganic coating applied to one or both surfaces. The inorganic coating layer comprises a plurality of inorganic particles and an adhesive. Here, the inorganic coating layer can comprise 80-99 wt% of a plurality of inorganic particles and 1-20 wt% of an adhesive. The inorganic coating layer of the separator according to the present invention is a one-sided or two-sided inorganic coating layer, preferably a two-sided coating, having a thickness of 0.5 μm-5 μm, preferably 0.5 μm-3 μm.
[0038] In the separator according to the present invention, the inorganic particles suitable for the inorganic coating layer are selected from the group consisting of Mg(OH)2, BaSO4, BaTiO3, HfO2, SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, boehmite (AlOOH), SiC, TiO2, and combinations thereof. Since the size of the gaps formed between the inorganic particles affects the battery characteristics, if the particle size of the inorganic particles is too large, the gaps between the particles will become too large, which may lead to short circuits caused by lithium dendrites. Therefore, the average particle size (D50) of the inorganic particles may be 0.1 μm to 2.0 μm, preferably 0.2 μm to 1.5 μm.
[0039] In the separator according to the present invention, the adhesive suitable for the inorganic coating layer is not particularly limited. Any known adhesive suitable for the field of separators can be used. For example, there is an adhesive having properties such as high electrochemical stability, excellent wettability to the electrolyte, and excellent chemical resistance. In one embodiment of the present invention, adhesives that can be used include, but are not limited to, ethylene-vinyl acetate copolymer, poly(meth)acrylate, crosslinkable (meth)acrylic resin, fluorine-based rubber, styrene-butadiene rubber, polyvinyl alcohol, polyvinyl butyral, polyvinylpyrrolidone, poly-N-vinylacetamide, polyvinylidene fluoride, polyurethane, or a combination thereof.
[0040] In the separator according to the present invention, the inorganic coating layer of the reinforced polyolefin porous substrate can be applied by a method known in the art, but is not particularly limited thereto, such as roll coating, doctor coating, dip coating, roller coating, spin coating, slit coating, and other coating methods commonly used in the art.
[0041] The separator according to the present invention has a resistance of 88 kgf / cm 2 After being compressed for 30 seconds under a load holding pressure of 1000 g / cm2, the compression resistance exceeds 90%, providing enhanced compression resistance. This suppresses stress-induced distortion of the separator pores and maintains ion conductivity in the thickness direction. After compression, the separator pores maintain a constant air permeability without excessive distortion due to stress, i.e., the air permeability (Gurley) decreases by less than 40%. This makes it possible to avoid an increase in resistance and internal pressure in the battery due to stress during use.
[0042] In this specification, "compression resistance" refers to the initial thickness (T1) and the compressibility of the separator at 88 Kgf / cm 2 The compression thickness (T2) measured after holding the load for 30 seconds is calculated according to the following formula: Sample compression ratio (%) = (T1-T2) / T1 x 100 Compression resistance = 100% - sample compression rate %
[0043] "Decrease in air permeability after compression (Gurley, sec / 100cc)" refers to a decrease in air permeability of the separator of 88 kgf / cm 2 This means that the physical structure was destroyed and the air permeability decreased after holding the load for 30 seconds. The calculation method is as follows: If the air permeability before compression is G1 and the air permeability after compression is G2, then the decrease in air permeability after compression (%) = (1-G1 / G2) x 100%.
[0044] The separator of the present invention has high temperature shrinkage resistance, provides high puncture strength, and has a high temperature burst temperature of greater than 160° C. The complete melting at high temperatures can prevent electrodes from contacting each other, thereby increasing the safety of the battery.
[0045] In another embodiment of the present invention, a method for producing a separator includes providing a polyolefin porous substrate, and subjecting the polyolefin porous substrate to a pre-strengthening treatment to form a reinforced polyolefin porous substrate. In the pre-strengthening treatment, a 0.1wt%-3wt% titanium alkoxide solution and a 30wt%-70wt% alcohol aqueous solution are sequentially applied to the polyolefin porous substrate, and an inorganic coating layer including a plurality of inorganic particles and an adhesive is applied to at least one surface of the reinforced polyolefin porous substrate.
[0046] In the manufacturing method according to the present invention, the titanium alkoxide solution used in the preliminary strengthening treatment is a methanol titanium solution, an ethanol titanium solution, a titanium isopropanol solution, a titanium (IV) t-butoxide solution, or a combination thereof, and is preferably titanium isopropanol. The solvent of the titanium alkoxide solution is methanol, ethanol, isopropanol, or a combination thereof. In one preferred embodiment of the present invention, the titanium alkoxide solution used in the preliminary strengthening treatment is preferably a 0.2wt% to 2.5wt% titanium alkoxide solution.
[0047] In the manufacturing method according to the present invention, the aqueous alcohol solution used in the preliminary strengthening treatment may be an aqueous methanol solution, an aqueous ethanol solution, an aqueous isopropanol solution, an aqueous ethoxyethanol solution, an aqueous allyl alcohol solution, an aqueous ethylene glycol solution, or a combination thereof. In a preferred embodiment of the present invention, the aqueous alcohol solution used in the preliminary strengthening treatment is an aqueous methanol solution, an aqueous ethanol solution, an aqueous isopropanol solution, or a combination thereof. In a preferred embodiment of the present invention, the aqueous alcohol solution is preferably an aqueous 40-60 wt % aqueous alcohol solution.
[0048] In the method for producing a separator according to the present invention, the titanium alkoxide solution used in the preliminary strengthening treatment further contains 0.5 wt% to 5 wt% of hexamethyldisilazane to stabilize the titanium alkoxide. The amount of the stabilizer in the titanium alkoxide solution is 0.5 wt% to 3 wt%, preferably 0.5 wt% to 2 wt%.
[0049] In the method for producing the separator according to the present invention, the alcoholic solution used in the preliminary strengthening treatment step further contains a tackifier. This strengthens the adhesion between the titanium oxide and / or titanium hydroxide formed by the reaction of the phthalic alkoxide with the alcoholic solution and the surface of the polyolefin porous substrate and the inner wall of the porous structure. Suitable tackifiers include, but are not limited to, poly(meth)acrylate resins, crosslinkable (meth)acrylic resins, poly N-vinylacetamide, acrylonitrile-acrylate copolymers, acrylonitrile-acrylamide-acrylate copolymers, or combinations thereof. In one preferred embodiment of the present invention, one or more tackifiers can be used in the alcoholic solution in the preliminary strengthening treatment.
[0050] In the method for producing the separator according to the present invention, the amount of the tackifier used in the preliminary strengthening treatment is 0.01 wt % to 1 wt %, preferably 0.05 wt % to 0.5 wt %, in the aqueous alcohol solution.
[0051] In the production method according to the present invention, the aqueous alcohol solution may further contain additives such as an antistatic agent, a flame retardant, an antioxidant, or a surface modifier, if necessary.
[0052] In the manufacturing method according to the present invention, the coating method in the preliminary strengthening treatment step may be a dip coating method or a spray coating method.
[0053] In the manufacturing method according to the present invention, the reinforced polyolefin porous substrate can have an inorganic coating layer applied to one or both surfaces thereof. The inorganic coating layer can include a plurality of inorganic particles and an adhesive. Here, the inorganic coating layer can include 80wt%-99wt% of the plurality of inorganic particles and 1wt%-20wt% of the adhesive.
[0054] In the manufacturing method of the present invention, the inorganic coating layer of the reinforced polyolefin porous substrate can be applied by a method known in the art, but is not particularly limited.For example, the coating method generally used in the art can include roll coating, doctor coating, dip coating, roller coating, spin coating, slit coating, etc.
[0055] The following examples are presented to further illustrate the present invention, but are not intended to limit the scope of the invention.
[0056] Working Example
[0057] Preparation Example: Preparation of Inorganic Particle Coating Solution
[0058] 38 g of aluminum oxide (CQ-030EN, purchased from Shandong China Porcelain Functional Materials Co., Ltd.), 3.4 g of polyacrylic acid ester, 0.68 g of ammonium polyacrylate (BYK-154, solid content 42%, purchased from BYK, Germany), 0.13 g of polyether-modified silicone surfactant (BYK-349, purchased from BYK, Germany) and 52.9 g of deionized water were mixed and stirred uniformly to obtain an inorganic particle coating solution.
[0059] Example 1: Preparation of a separator
[0060] 4g of titanium isopropanol was added to 196g of 99.5% anhydrous ethanol, and mixed uniformly, and stirred at room temperature to obtain a titanium isopropanol solution. 98.4g of deionized water and 98.4g of 95% ethanol were mixed uniformly to obtain an aqueous ethanol solution.
[0061] A 9 μm thick polyethylene porous substrate (porosity 48%) was immersed in the titanium isopropanol solution of this example for 1 minute, and excess droplets were removed with a doctor blade. The substrate was then immersed in an aqueous ethanol solution, and the polyethylene porous substrate was removed and dried at 80 ° C. to obtain a reinforced polyethylene porous substrate.
[0062] The inorganic particle coating solution prepared in Preparation Example 1 was applied to the obtained reinforced polyethylene porous substrate and dried. An inorganic coating layer having a thickness of 2 μm was formed on each of the two opposing surfaces of the reinforced polyethylene porous substrate, and a separator having a total thickness of 13 μm was obtained.
[0063] The separator thus obtained was measured by the method described below. The measurement results are shown in Table 1.
[0064] Thickness measurement: Based on the GB / T6672-2001 measurement standard, the thickness was measured using a film thickness gauge (VL-50-B, purchased from Mitutoyo, Japan). The measurement was performed using a flat probe with a diameter of 3 mm and a down pressure probe load of 0.01 N.
[0065] Air permeability (Gurley) measurement: The separator to be measured was cut into pieces of 1 square inch according to the ASTM D-726 standard, and the time required for 100 cc of air to pass through the separator to be measured was measured using a Gurley air permeability meter to obtain the air permeability.
[0066] Thermal shrinkage measurement: A 10cm x 10cm sample was cut, and the initial lengths M0 and T0 in the machine direction (MD) and transverse direction (TD) were marked at the center of the sample before measurement. After marking, the sample was sandwiched between two sheets of A4 paper and placed in an oven and heated at 150°C for 1 hour. After heating, the sample was left for 30 minutes in the same environment as the measuring instrument, and the length M1 in the machine direction (MD) and the length T1 in the transverse direction (TD) at the center of the sample were measured. Thermal shrinkage rate in machine direction (MD) (SMD) = (M0-M1) / M0 x 100% Transverse direction (TD) thermal shrinkage rate (STD) = (T0-T1) / T0 x 100%
[0067] Tensile strength measurement: According to ASTM D882-09 standard, the separator to be measured was cut into a size of 10 mm width and ≥ 150 mm length in each machine direction (MD) and transverse direction (TD), and pulled at a speed of 500 mm / min using a universal tensile machine to obtain the maximum load value at which the sample broke. The maximum load value was then divided by the cross-sectional area of the separator (sample width x substrate thickness) to calculate the tensile strength of the separator in the machine direction (MD) and transverse direction (TD), respectively.
[0068] Puncture resistance (gf): The puncture strength was measured using a tensile tester (MSG-5, purchased from Kato Tech, Japan). A round-headed stainless steel needle with a needle diameter of 1 mm and R angle of 0.5 mm was used to pierce the sample to be measured at a measurement speed of 100±10 mm / min, and the maximum force (gf) required to pierce the separator to be measured was recorded.
[0069] Absorption rate measurement: The separator to be measured was cut into a size of 80 mm x 10 mm, and the sample was suspended vertically in an enclosed space and immersed in a solvent (a mixture of propylene carbonate (PC) and diethyl carbonate (DEC) in a weight ratio of 1:1). The initial liquid level was marked on the sample, and the height (mm) of capillary absorption of the separator was recorded after 1 minute, starting from the line indicating the initial liquid level.
[0070] Contact angle measurement: The contact angle was measured using a contact angle meter (Phoenix 150, purchased from Seiko Technology, Taiwan). A syringe barrel with a needle diameter of 2 mm was used to suck up propylene carbonate (PC, purity 99%) and place it in the meter, the separator sample to be measured was fixed on the sample mounting stage, the volumetric liquid was pushed out of the syringe barrel and dropped onto the sample to be measured, the measurement was performed using the optical CCD, and the contact angle was calculated using computer software.
[0071] Impedance measurement: A separator sample with a diameter of 24 mm was cut and soaked in an electrolyte for 10 minutes. The sample was then sandwiched between two stainless steel electrodes, which were then separated and pressed with a weight of 500 g to bring the sample into close contact. The current signal was measured using an AC impedance analyzer, and the impedance value of the separator sample was calculated.
[0072] Crack measurement: A 3cm x 20cm separator sample was cut out and placed in a 200°C oven for 1 hour. After removal, it was visually inspected for cracks. "X" indicates that there was a crack, "△" indicates that it was impossible to judge because the separator had shrunk, and "·" indicates that there was no crack.
[0073] Melt Integrity: A separator sample with a length of 8 mm and a width of 4.5 mm was cut and placed in the sample chamber of a thermomechanical analyzer (TMA 450, purchased from TA Instruments, USA). The sample was heated to 200°C at a rate of 5°C / min under a load of 0.01N, and the rupture temperature was recorded after the measurement was completed. Here, under a fixed load of 0.01N, the separator is judged to have ruptured when it reaches its heat-receiving limit and the shape deformation reaches a maximum value with the increase in temperature. The temperature point of rupture is defined as the rupture temperature.
[0074] Compression resistance: 50 pieces of 4cm x 4cm separation membrane were cut out and stacked as samples, and the initial thickness (T1) was measured as described above and placed in the jig. 2 The load was applied, and the holding pressure was stopped after 30 seconds. After the end of the load, the compressed thickness (T2) of the sample was measured and calculated according to the following formula: Sample compression ratio (%) = (T1-T2) / T1 x 100 Compression resistance = 100% - sample compression rate %
[0075] Air permeability after compression: Air permeability (G1) was measured according to the above measurement method for measuring air permeability, and then the sample was compressed using the above measurement method for compression resistance, and the air permeability after compression (G2) was measured according to the above measurement method for measuring air permeability, and calculated according to the following formula: Percentage decrease in air permeability after compression (%) = (1-G1 / G2) x 100%
[0076] Example 2: Preparation of a separator
[0077] 1.6g of titanium isopropanol and 2g of hexamethyldisilazane were added to 196.4g of 99.5% anhydrous ethanol, mixed uniformly, and stirred at room temperature to obtain a titanium isopropanol solution. 98.4g of deionized water and 98.4g of 95% ethanol were mixed uniformly, 3g of poly-N-vinylacetamide (PNVA GE191-107, solid content 10%, purchased from Showa Denko K.K., Japan) was added, stirred uniformly at room temperature, and 0.13g of polyacrylate (BM-950B, solid content 39%, purchased from Zeon Co., Ltd.) was added, and stirred at room temperature to obtain an ethanol aqueous solution.
[0078] A 9 μm thick polyethylene porous substrate (porosity 48%) was immersed in the titanium isopropanol solution of this example for 1 minute, and after removing excess droplets with a doctor blade, it was immersed in an ethanol aqueous solution. The polyethylene porous substrate was removed and dried at 80 ° C to obtain a reinforced polyethylene porous substrate.
[0079] The inorganic particle coating solution prepared in Preparation Example 1 was applied to the obtained reinforced polyethylene porous substrate and dried. An inorganic coating layer having a thickness of 2 μm was formed on each of the two opposing surfaces of the reinforced polyethylene porous substrate, to obtain a separator having a total thickness of 13 μm.
[0080] The obtained separator was measured by the measurement method described below. The measurement results are shown in Table 1.
[0081] Example 3: Preparation of a separator
[0082] 0.8g of titanium isopropanol and 2g of hexamethyldisilazane were added to 197.2g of 99.5% anhydrous ethanol, mixed uniformly, and stirred at room temperature to obtain a titanium isopropanol solution. 98.4g of deionized water and 98.4g of 95% isopropanol were mixed uniformly, 3g of poly-N-vinylacetamide (PNVA GE191-107) was added, stirred uniformly at room temperature, and 0.13g of polyacrylate (BM-950 B) was added, and stirred at room temperature to obtain an ethanol aqueous solution.
[0083] A 9 μm thick polyethylene porous substrate (porosity 48%) was immersed in the titanium isopropanol solution of this example for 1 minute, and excess droplets were removed with a doctor blade. The substrate was then immersed in an aqueous isopropanol solution, and the polyethylene porous substrate was removed and dried at 80 ° C to form a reinforced polyethylene porous substrate.
[0084] The inorganic particle coating solution prepared in Preparation Example 1 was applied to a reinforced polyethylene porous substrate and dried. An inorganic coating layer having a thickness of 2 μm was formed on each of the two opposing surfaces of the reinforced polyethylene porous substrate. The total thickness of the reinforced polyethylene porous substrate including both coating layers was 13 μm.
[0085] The obtained separator was measured by the measurement method described below. The measurement results are shown in Table 1.
[0086] Example 4: Preparation of a separator
[0087] 1.6g of titanium isopropanol and 2g of hexamethyldisilazane were added to 196.4g of 99.5% anhydrous ethanol, mixed uniformly, and stirred at room temperature to obtain a titanium isopropanol solution. 98.4g of deionized water and 98.4g of 95% isopropanol were mixed uniformly, 3g of poly-N-vinylacetamide (PNVA GE191-107) was added, stirred uniformly at room temperature, and 0.13g of polyacrylate (BM-950B) was added, and stirred at room temperature to obtain an ethanol aqueous solution.
[0088] A 9 μm thick polyethylene porous substrate (porosity 48%) was immersed in the titanium isopropanol solution of this example for 20 seconds, and excess droplets were removed with a doctor blade. The substrate was then immersed in an aqueous isopropanol solution, and the polyethylene porous substrate was removed and dried at 80 ° C. to form a reinforced polyethylene porous substrate.
[0089] The inorganic particle coating solution prepared in Preparation Example 1 was applied to a reinforced polyethylene porous substrate and dried. An inorganic coating having a thickness of 2 μm was formed on each of the two opposing surfaces of the reinforced polyethylene porous substrate. The total thickness of the polyethylene porous substrate including both coating layers was 13 μm.
[0090] The obtained separator was measured by the measurement method described in Example 1. The measurement results are shown in Table 1.
[0091] Comparative Example 1
[0092] A polyethylene porous substrate having a thickness of 9 μm (porosity: 48%) similar to that of Example 1 was obtained, and the inorganic particle coating liquid prepared in Preparation Example 1 was applied to the polyethylene porous substrate that had not been pre-reinforced, followed by drying.
[0093] An inorganic coating layer having a thickness of 2 μm was formed on both sides of the polyethylene porous substrate. The total thickness of the polyethylene porous substrate including both coating layers was 13 μm. Measurement was performed according to the measurement method described in Example 1. The measurement results are shown in Table 1. Table 1: Measurement results of separator properties in Examples 1 to 4 and Comparative Example 1 [Table 1]
[0094] In the separator according to the present invention, a reinforced polyolefin porous substrate is formed by pre-strengthening the polyolefin porous substrate, and an inorganic coating layer is applied to the substrate. This increases the mechanical strength of the polyolefin porous substrate, and the separator's tensile strength, puncture strength, and compression resistance can be enhanced without increasing the total thickness of the separator. As in the above-mentioned example, taking a separator having a 9 μm polyolefin porous substrate and 2 μm inorganic coating layers applied to both surfaces, the elongation of the polyolefin porous substrate not pre-strengthened in both the machine direction (MD) and the transverse direction (TD) is 1400 kgf / cm. 2 On the other hand, the separator having a reinforced polyolefin porous substrate and an inorganic coating layer according to the present invention has an elongation of 1450 kgf / cm in both the machine direction (MD) and the transverse direction (TD). 2 The puncture strength is improved to above 400 gf, and the separator according to the present invention has a compression resistance of more than 90%. Therefore, the separator according to the present invention can enhance the tensile strength and compression resistance of the separator without increasing the total thickness of the separator.
[0095] Although the embodiments of the present invention are disclosed as above, they are not used to limit the present invention. Anyone familiar with this technology can make various modifications and finishings without departing from the spirit and scope of the present invention. The protection scope of the present invention is subject to what is defined by the appended claims.
Claims
1. A separator, A reinforced polyolefin porous substrate obtained by subjecting a polyolefin porous substrate to a pre-reinforcing treatment; an inorganic coating layer formed on at least one surface of the reinforced polyolefin porous substrate, the inorganic coating layer comprising a plurality of inorganic particles and an adhesive; Equipped with The pre-strengthening treatment includes sequentially applying a 0.1 wt % to 3 wt % titanium alkoxide solution and a 30 wt % to 70 wt % aqueous alcohol solution to a polyolefin porous substrate.
2. 2. The separator according to claim 1, wherein the pre-strengthening treatment comprises applying a 0.2 wt % to 2.5 wt % titanium alkoxide solution and a 40 wt % to 60 wt % alcohol aqueous solution to the polyolefin porous substrate.
3. 2. The separator according to claim 1, wherein the titanium alkoxide solution used in the pre-strengthening treatment further contains 0.5 wt % to 5 wt % hexamethyldisilazane.
4. The separator according to claim 1 , wherein the alcohol-water solution used in the pre-strengthening treatment further comprises a tackifier.
5. The separator according to claim 4, wherein the amount of the tackifier used is 0.01 wt % to 1 wt %.
6. 5. The separator of claim 4, wherein the tackifier is poly(meth)acrylate, poly N-vinylacetamide, crosslinkable (meth)acrylic resin, acrylonitrile-acrylate copolymer, acrylonitrile-acrylamide-acrylate copolymer, or a combination thereof.
7. The separator according to claim 1 , wherein the polyolefin porous substrate is a single layer polyethylene or a single layer polypropylene.
8. 2. The separator of claim 1, wherein the inorganic coating layer comprises 80 wt% to 99 wt% of a plurality of inorganic particles and 1 wt% to 20 wt% of an adhesive.
9. The inorganic particles in the inorganic coating layer are Mg(OH) 2 , BaSO 4 , BaTiO 3 , HfO 2 , SrTiO 3 , SnO 2 , CeO 2 , MgO, NiO, CaO, ZnO, ZrO 2 , SiO 2 , Y 2 O 3 , Al(OH) 3 , Al 2 O 3 , boehmite (AlOOH), SiC, TiO 2 or a combination thereof.
10. 9. The separator according to claim 8, wherein the adhesive in the inorganic coating layer is ethylene-vinyl acetate copolymer (EVA), poly(meth)acrylate, cross-linkable (meth)acrylic resin, fluorine-based rubber, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinylpyrrolidone (PVP), poly-N-vinylacetamide, polyvinylidene fluoride (PVDF), polyurethane, or a combination thereof.
11. The separator has a strength of 88 kgf / cm 2 2. The separator of claim 1, having a compression resistance of greater than 90% after being held at a load of 0.1 μm for 30 seconds.
12. The separator has a strength of 88 kgf / cm 2 2. The separator according to claim 1, wherein the decrease in air permeability (Gurley) after holding the load at 1000 psi for 30 seconds is less than 40%.
13. 10. The separator of claim 1, wherein the separator has a hot burst temperature greater than 160°C.
14. A method for producing a separator, comprising the steps of: A polyolefin porous substrate is provided; pre-strengthening the polyolefin porous substrate to form a reinforced polyolefin porous substrate; Applying an inorganic coating layer comprising a plurality of inorganic particles and an adhesive to at least one surface of the reinforced polyolefin porous substrate. Including, The pre-strengthening treatment includes applying a 0.1 wt % to 3 wt % titanium alkoxide solution and a 30 wt % to 70 wt % alcohol aqueous solution to the polyolefin porous substrate.
15. The titanium alkoxide in the titanium alkoxide solution in the preliminary strengthening treatment is methanol titanium, ethanol titanium, titanium isopropanol, and titanium (IV) t-butoxide or a combination thereof; The method according to claim 14, wherein the solvent of the titanium alkoxide solution is methanol, ethanol, or isopropanol, or a combination thereof.
16. 15. The method of claim 14, wherein the alcohol aqueous solution in the preliminary strengthening treatment is methanol, ethanol, isopropanol, ethoxyethanol, allyl alcohol, ethylene glycol, or a combination thereof.
17. The titanium alkoxide solution contains 0.2 wt % to 2.5 wt % of titanium alkoxide solution; The alcohol aqueous solution contains 40 wt % to 60 wt % of an alcohol aqueous solution. The method of claim 14.
18. The manufacturing method according to claim 14, wherein the titanium alkoxide solution used in the pre-strengthening treatment further contains 0.5 wt% to 5 wt% hexamethyldisilazane.
19. The method according to claim 14, wherein the alcoholic aqueous solution used in the preliminary strengthening treatment further contains a tackifier in an amount of 0.01 wt% to 1 wt% in the alcoholic aqueous solution.
20. 20. The method of claim 19, wherein the tackifier is a poly(meth)acrylate resin, a crosslinkable (meth)acrylic resin, poly N-vinylacetamide, an acrylonitrile-acrylate copolymer, an acrylonitrile-acrylamide-acrylate copolymer, or a combination thereof.